Anti-inflammatory effect of D-pinitol isolated from the leaves of Colutea cilicica Boiss et Bal. on K562 cells - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2017)
Aim: D-pinitol, a natural compound has shown various biological and pharmacological effects. Last studies are focused on the determination of its further pharmacological activities including mainly biological activity. Therefore, isolation of D-pinitol from the leaves of Colutea cilicica Boiss et Bal. and investigation of its apoptotic and anti-inflammatory activity on K562 cell lines were aimed in the concept of the study. Materials and methods: Isolation of D-pinitol was performed by column chromatography. Chemical structure of the compound was confirmed by spectroscopic methods including 1H NMR, 13C NMR, 2D NMR, HPLC-TOF/MS, and IR. Cell viability was evaluated by dose and time dependent in K562 cell lines. D-pinitol was isolated from C. cilicica leaves for the first time. Results: Stimulation of cells with D-pinitol (0-80 M) was observed for 24, 48 and 72 h. It is determined that D-pinitol inhibited protein expression of Cox-2 in K562 cells. We observed that Poly (ADP-ribose) polymerase (PARP) protein expression did not change, but Cox-2 protein expression reduced with non-cytotoxic concentrations of D-pinitol. Conclusion: It is concluded that D-pinitol did not affect cell proliferation and apoptosis in K562 cells however reduced the inflammation, significantly. These results show that D-pinitol may be anti-inflammatory agent for the treatment of K562 cells.
Keywords: Anti-inflammatory activity; K562; Colutea cilicica Boiss et Bal.; Isolation; D-pinitol; FACTOR-KAPPA-B; INHIBITION; ACTIVATION; APOPTOSIS; PRODUCTS; INVASION